Psicanálise e hospital: há ato analítico? : estudo sobre a especificidade da intervenção psicanalítica na pediatria e seus efeitos no tratamento da criança hospitalizada - Arleta Maria Serra Carvalho (2011)
The present dissertation is the result of a Masters research that interrogates if thepsychoanalytical act is possible in a General Hospital. Based on the practice of the psychoanalyst in the Pediatrics ward of the Federal University of Minas Gerais Hospital das Clínicas, we start from a reflection on this practice, taking particularly into account the effects of the hospitalized child on the child itself, on his family and on the staff. Death in the child unravels a devastating real in so far as it confronts the parents narcissistic ideal, as well as it convokes in the family and in the staff a feeling of impotence. In a hospital, the psychoanalyst seeks to reduce the impotence to its degree of impossibility. We question the medical demand, separating it from the subjects demand and, further more, we aim to point out the gap between demand and desire. The psychoanalytical ethics involves a commitment with the subjects desire, giving treatment to the anxiety that paralyses him, blurring speeches, sustaining him in the symbolic. We recur to Lacans work The Seminar, book 15: The Psychoanalytical Act to verify what has Lacan formalized on the process of a standard analysis and on what he called psychoanalytical act. The question that would come to be outlined would be if Psychoanalysis, transported to other practices as the institutional ones, articularly in the hospital context, would sustain itself. We do not utilize the psychoanalytical act scheme with the intention of making it fit the pediatric-hospital practice, but to identify convergence and divergence points between the same, even because Psychoanalysis, in the contemporaneity, needs to advance beyond the established parameters. We utilize, thus, some clinical cases attended in this context so that we could put to the test the question that presented itself since the beginning of this dissertation: is there an analytical act in an hospital? From this exposure, we conclude that Psychoanalysis is not only possible in an hospital, but fundamental, in so far as it sustains that there is a desiring subject beyond the suffering body and that this subject has something to tell us, attitude that is essential to the conduct of an entire staff.